Pemanfaatan Artificial Intellegence dalam Pembelajaran Matematika - Badri, Fawaidul (Galois: Jurnal Penelitian Pendidikan Matematika, 2024)
Since ChatGPT was known as artificial intelligence and its massive development from year to year has had a big impact on various aspects of life. The impact provided by artificial intelligence is increasingly visible from the presence of increasingly advanced features, functions and appearance. Its use in the educational sector cannot be separated from advances in artificial intelligence. For some teachers and students, the term artificial intelligence is still very new, as is its use in the teaching and learning process. Currently, there are still many obstacles and challenges that cannot be denied, related to the use of artificial intelligence in Indonesia. However, in the world of global education, it is increasingly common to utilize artificial intelligence in the teaching and learning process. The introduction of artificial intelligence to junior high school students is considered very appropriate, because the psychology of students at this level is more developed, and also the learning load is starting to increase compared to elementary level. Mathematics subjects for most students are still a scourge. In this research, artificial intelligence was introduced to class X students at SMAN 1 Kedungdung which is related to mathematics learning so that it can help in student learning. The results of the evaluation of the implementation of the service show high student enthusiasm regarding the use of artificial intelligence either to help with learning or for other purposes. Keywords: Aritificial Intellegence, Learning, Mathematics